Takotsubo syndrome after mitral valve replacement and defibrillation - E. A. Zakharian; P. E. Grigoriev; D. V. Shatov (Бюллетень сибирской медицины)
The article describes the case of Takotsubo syndrome, which arose in a 71-year-old female patient after a mitral heart valve replacement , performed due to its severe (3rd degree) insufficiency of non-rheumatic genesis. This pathology is quite rare. Questions of its etiology and pathogenesis remain controversial. A special feature of this case is the development of reversible left ventricular dysfunction in the early postoperative period after mitral valve replacement. The reduction of the left ventricular ejection fraction to 25% with hyperkinesia of its basal parts with subsequent recovery of the ejection fraction to 56% 3 weeks after the onset of the disease was observed. There were also electrocardiographic changes simulating acute circular myocardial infarction with the absence of hemodynamically significant lesions of the coronary arteries. The patient had risk factors for this syndrome (age, female gender, stress situation, surgical intervention, administration of dobutamine and fluoroquinolones). For the reasons given above, the presence of Takotsubo syndrome was suspected. This case demonstrates the possibility of developing takotsubo syndrome after cardiosurgical interventions and defibrillation.